Coronavirus 2019 and People Living With Human Immunodeficiency Virus: Outcomes for Hospitalized Patients in New York City. (28th June 2020) - Sigel, Keith; Swartz, Talia; Golden, Eddye; Paranjpe, Ishan; Somani, Sulaiman; Richter, Felix; De Freitas, Jessica K; Miotto, Riccardo; Zhao, Shan; Polak, Paz; Mutetwa, Tinaye; Factor, Stephanie; et al.
Abstract: Background: There are limited data regarding the clinical impact of coronavirus disease 2019 (COVID-19) on people living with human immunodeficiency virus (PLWH). In this study, we compared outcomes for PLWH with COVID-19 to a matched comparison group. Methods: We identified 88 PLWH hospitalized with laboratory-confirmed COVID-19 in our hospital system in New York City between 12 March and 23 April 2020. We collected data on baseline clinical characteristics, laboratory values, HIV status, treatment, and outcomes from this group and matched comparators (1 PLWH to up to 5 patients by age, sex, race/ethnicity, and calendar week of infection). We compared clinical characteristics and outcomes (death, mechanical ventilation, hospital discharge) for these groups, as well as cumulative incidence of death by HIV status. Results: Patients did not differ significantly by HIV status by age, sex, or race/ethnicity due to the matching algorithm. PLWH hospitalized with COVID-19 had high proportions of HIV virologic control on antiretroviral therapy. PLWH had greater proportions of smoking ( P < .001) and comorbid illness than uninfected comparators. There was no difference in COVID-19 severity on admission by HIV status ( P = .15). Poor outcomes for hospitalized PLWH were frequent but similar to proportions in comparators; 18% required mechanical ventilation and 21% died during follow-up (compared with 23% and 20%, respectively). There was similar cumulative incidence of death over time by HIV status ( P = .94). Conclusions: We found no differences in adverse outcomes associated with HIV infection for hospitalized COVID-19 patients compared with a demographically similar patient group. Abstract : There are limited data on coronavirus disease 2019 (COVID-19) clinical outcomes for people living with human immunodeficiency virus (PLWH). We report outcomes for a cohort of hospitalized PLWH with COVID-19 compared with demographically matched comparators. Major adverse outcomes were similar for PLWH and matched comparators.